Signaling Inclusivity: Unveiling the Determinants of Corporate LGBTQIA+ Inclusivity Through Signaling Theory - Siuta, Kinga (Sygnalizowanie inkluzywności: Determinanty inkluzywności korporacyjnej wobec osób LGBTQIA+ w ramach teorii sygnalizacji, 2024)
Aim: This study aims to explore how U.S. corporations signal their commitment to LGBTQ+ inclusivity, using signaling theory as a framework. Methodology: By analyzing a dataset of 700 companies and utilizing the Corporate Equality Index (CEI) from the Human Rights Campaign, the research examines the role of sector characteristics and voluntary participation in inclusivity efforts. Results: Through univariate analysis, instrumental variable (IV) regression, and Structural Equation Modeling (SEM), the study finds that consumer-facing sectors tend to signal a stronger commitment to inclusivity, reflected in higher CEI scores, while sectors with high injury risks show weaker or inverse correlations with inclusivity. Additionally, the findings highlight that the authenticity of inclusivity efforts – particularly voluntary reporting – is crucial, suggesting that genuine engagement, rather than mere compliance, enhances the effectiveness of inclusivity signaling. Implications and recommendations: The implications for researchers include a deeper understanding of how sector dynamics and voluntary actions influence corporate inclusivity, while practitioners are advised to prioritize authentic engagement to effectively communicate their inclusivity values to stakeholders. Originality/value: This research contributes to the literature by emphasizing the strategic importance of authentic inclusivity signaling in shaping corporate culture and external perceptions.
Econometrics = Ekonometria, 2024, Vol. 28, No. 4, s. 1-22
Keywords: Corporate Equality Index; signaling theory; corporate inclusivity policies; CSR; Indeks Równości Korporacyjnej; teoria sygnalizacji; korporacyjne polityki inkluzywności